Thinking critically about ethical issues - Ruggiero, Vincent Ryan (McGraw Hill, 2011)
Emphasizes doing ethical analysis and thinking critically about ethical issues, rather than focusing on ethical theory or the history of ethics. This title helps readers apply ethical principles to issues that exemplify the kinds of moral challenges encountered in everyday life.